Developing Public Relations Curricula in Agricultural Communications - Shelly Sitton; D. Dwayne Cartmell; Sarah Sargent (Journal of Applied Communications, 2005)
Agricultural public relations professionals were surveyed to determine the proficiencies in public relations that they perceive to be most important in an agricultural communications curriculum. They also were asked how frequently they used those proficiencies and how best to integrate the proficiencies in the agricultural communications curriculum. The population for the study consisted of public relations professionals who were members of the Agricultural Relations Council and the Cooperative Communicators Association. Most respondents perceived agricultural proficiencies to be less important than general communications or public relations proficiencies. Proficiencies related to use of the computer skills, human relations skills, time management, writing, and editing were among the most frequently used proficiencies by public relations professionals. Based on these results, it is recommended that university faculty consider focusing public relations curriculum toward writing, editing, presentations, time management, conflict resolution, and teamwork. It also is recommended that students take coursework in agricultural policy and government programs and finance/business principles. Finally, it is recommended that faculty stress the importance of meeting deadlines to prepare students for the public relations profession.